Cardiovascular health and potential cardiovascular risk factors in young athletes - Grabitz, Carl; Sprung, Katharina M.; Amagliani, Laura; Memaran, Nima; Schmidt, Bernhard M. W.; Tegtbur, Uwe; von der Born, Jeannine; Kerling, Arno; Melk, Anette (Frontiers in Cardiovascular Medicine, 2023)
Introduction Cardiovascular disease remains the most common cause of death worldwide, and early manifestations are increasingly identified in childhood and adolescence. With physical inactivity being the most prevalent modifiable risk factor, the risk for cardiovascular disease is deemed low in people engaging in regular physical exercise. The aim of this study was to investigate early markers and drivers of cardiovascular disease in young athletes pursuing a career in competitive sports. Methods One hundred and five athletes (65 males, mean age 15.7 ± 3.7 years) were characterized by measurement of body impedance to estimate body fat, blood pressure (BP), carotid femoral pulse wave velocity (PWV) to evaluate arterial elasticity, ergometry to assess peak power output, echocardiography to calculate left ventricular mass, and blood tests. Results Systolic BP was elevated in 12.6% and thereby more than twice as high as expected for the normal population. Similarly, structural vascular and cardiac changes represented by elevated PWV and left ventricular mass were found in 9.5% and 10.3%. Higher PWV was independently associated with higher systolic BP (β = 0.0186, p < 0.0001), which in turn was closely correlated to hemoglobin levels (β = 0.1252, p = 0.0435). In this population, increased left ventricular mass was associated with lower resting heart rate (β = −0.5187, p = 0.0052), higher metabolic equivalent hours (β = 0.1303, p = 0.0002), sport disciplines with high dynamic component (β = 17.45, p = 0.0009), and also higher systolic BP (β = 0.4715, p = 0.0354). Conclusion Despite regular physical exercise and in the absence of obesity, we found an unexpected high rate of cardiovascular risk factors. The association of PWV, systolic BP, and hemoglobin suggested a possible link between training-induced raised hemoglobin levels and altered vascular properties. Our results point toward the need for thorough medical examinations in this seemingly healthy cohort of children and young adults. Long-term follow-up of individuals who started excessive physical exercise at a young age seems warranted to further explore the potential adverse effects on vascular health.